Overview Juridical Liberation Conditional for Convict in System Indonesian Criminal Justice - Fakhraiulza Cesar Rahardian (UM Purwokerto Press, 2023)
The penal system in Indonesia still applies the practice of parole with various provisions which are crucial elements in releasing convicts. Conditional release can be given to convicts who have met certain requirements based on the provisions of Article 15 of the Criminal Code, namely if the defendant has served 2/3 (two thirds) of his sentence or at least 9 (nine) months of the sentence handed down. The purpose of this study is to find out and analyze the implementation of parole for convicts based on the criminal system in Indonesia by taking into account the Criminal Code and the Correctional Law. The formulation of the problem in this study is a) What are the procedures and conditions for parole for convicts in Indonesia? B) What is the Juridical Review of Parole Release for Convicts in the Indonesian Penal System? This study uses a normative research method with a Statutory Approach through descriptive-analytical research specifications. The basic considerations for the implementation of parole are relevant to the Correctional Law regarding the purpose of sentencing. The implementation of parole must pay attention to social benefits and values ??so that the enforcement of prisoners' rights will be in accordance with the needs of society in general.